'Where were your clothes?' Eliciting descriptions of clothing placement from children alleging sexual abuse in criminal trials and forensic interviews. (1st June 2016) - Stolzenberg, Stacia N.; Lyon, Thomas D.
Abstract : Purpose: This study examined how children alleging sexual abuse are asked about clothing placement during abusive episodes, both in criminal trials and forensic interviews. The placement of clothing is of great importance, because it facilitates distinguishing abusive touch from non‐abusive touch, as well as the severity of abuse when the touching is in fact sexual. If clothing has not been removed, then sexual abuse appears less likely and certain types of sexual contact are physically impossible (or at least highly improbable). Methods: We examined how trial attorneys ( n  =   142) and forensic interviewers in investigative interviews ( n  =   155) questioned 5‐ to 12‐year‐olds about the location of clothing during alleged sexual abuse. To do so, we identified all question–answer pairs that included references to clothing placement, and coded for the clothing item mentioned, whether the interviewer elicited information about clothing placement or the child spontaneously provided such information, question type, and response type. Results: Discussions about clothing placement were commonplace in both settings, particularly in court. Fewer than one in five question–answer pairs about clothing placement were spontaneous mentions by children; the questioner elicited most discussions. When interviewers asked wh‐ questions rather than yes/no and forced‐choice questions, children provided more elaboration, more detailed clothing information, and were over six times more likely to describe clothing placement in a fashion that could not be captured by a single preposition (e.g., neither on nor off). Conclusions: The findings suggest that descriptions of clothing placement are subject to serious misinterpretation when closed‐ended questions are asked.